Exploration of Dynamic Query Suggestions and Dynamic Search Results for Their Effects on Search Behaviors - Gonzalez-Ibanez, R (2012)
While search behavior using dynamic query suggestions is understudied, it is virtually non-existent for dynamic search results (as currently experienced with Google Instant). We report results from a controlled lab study aimed at exploring the effects of these recent search interface developments - dynamic query suggestions and dynamic search results - on users search behaviors. Based on the availability of these two features, 36 participants were assigned to three conditions and were asked to complete an exploratory search task. Analyses on user behaviors were conducted based on log data, screen videos, and eye tracking. Our results showed that while the dynamic search results feature exposed the participants to more search results pages, shorter querying time and shorter queries, such a functionality did not change users general search process transition, as well as number of search sites, queries, and visited webpages. The findings also indicate a need to evaluate search interface features in the broader context of task completion rather than information searching and query running only. Copyright 2012 Chirag Shah and Roberto González-Ibáñez of Rutgers University, and Jingjing Liu of University of South Carolina.